Pengembangan E-Modul Berbasis Aplikasi Android Pada Mata Kuliah Teknologi Informasi Komunikasi Pendidikan Jasmani Program Studi PJKR FIK UNIMED - Siregar, Abdul Hakim; Fahrian, Muhammad Andri (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The aim of the basic research is to produce an Android application-based product for the Physical Education Information Communication Technology Subject, PJKR FIK Unimed Study Program, which is valid and effective. This research uses the Research and Development (R&D) research and development method. The ADDIE development model consists of five stages which include analysis, design, development, implementation and evaluation. The location of the research was carried out at the Unimed PJKR Study Program. The 2020 Regular class A research subjects consisted of 30 students. Data collection techniques in this research used questionnaires and tests. The instrument used to collect data during the Android Application-based E-Module Development process in the Physical Education Information Communication Technology Subject, PJKR FIK Unimed Study Program is in the form of a questionnaire from material and media experts. The data obtained then researchers analyzed qualitatively and quantitatively. The research results of Android application-based products in the Physical Education Information Communication Technology Course, PJKR FIK Unimed Study Program are valid and suitable for use in lectures, in accordance with research findings and analysis. 80% of materials expert feasibility study findings show that the product can be used without modification. Media expert validation results show that 95% of product input can be used without modification. The overall average validation of Android Application-Based E-Modules in the Physical Education Information Communication Technology Subjects of the PJKR study program is 87.5%. The results of the product effectiveness test showed changes in student scores between before and after using the teaching materials. The average score obtained during the pre-test was 57.85, while during the post-test the average score obtained was 90.42. The conclusion is that the Android application-based product in the Physical Education Information Communication Technology Subject, PJKR FIK Unimed Study Program is valid and effective.